Reign of God, Trinity, or Promise? Alternative Missiological Keys for Engaging Religious Pluralism. Issue 2 (June 2015) - Kääriäinen, Jukka
Abstract The fact of religious pluralism demands a theological response. Recent models for engaging religious pluralism overcome the shortcomings of traditional models. However, they inadequately address the categories of sin and divine hiddenness, while struggling to articulate a coherent relationship between dialogue and proclamation. The classic Lutheran tradition offers three fruitful resources (the gospel as promise, the law/gospel distinction, and the hiddenness of God) for engaging religious pluralism and balancing interreligious dialogue and gospel proclamation.